Stability of phenolic compounds and drying characteristics of apple peel as affected by three drying treatments - Qiancheng Ma; Jinfeng Bi; Jianyong Yi; Xinye Wu; Xuan Li; Yuanyuan Zhao (Food Science and Human Wellness)
To realize high-value utilization of discarded apple peel, this study investigated the effects of three selected commercial drying methods on drying kinetics, microstructure, color, phenolic stability and antioxidant capacity of apple peel. Apple peel was dehydrated by hot air drying (AD) at 75, 65 and 55 °C, heat pump drying (HP) at 65, 55 and 45 °C, and vacuum freeze-drying (FD), respectively. The results showed that HP was superior to AD and FD in terms of drying rate. In addition, HP at 65 °C provided high-quality dried apple peel due to less browning and brighter appearance, the highest retention of total phenolics (29.35 mg/g) and the strongest antioxidant activities, with the highest ABTS and FRAP value of 127.15 and 219.57 μmol TE/g, respectively. The content of the six major individual phenolics, i.e. caffeic acid, (-)-epicatechin, hyperoside, rutin, phlorizin and quercitrin, were found to be the highest in HP dried samples. Interestingly, the content of rutin was even increased after HP compared to the fresh sample. Considering drying efficiency, organoleptic quality and phenolic stability of the products, HP at 65 °C is suggested for drying of apple peel.